Nonadecadienone, a new termite trail-following pheromone identified in Glossotermes oculatus (Serritermitidae) - Hanus, Robert; Šobotník, Jan; Krasulová, Jana; Jiroš, Pavel; Žáček, Petr; Kalinová, Blanka; Dolejšová, Klára; Cvačka, Josef; Bourguignon, Thomas; Roisin, Yves; Lacey, Michael J; Sillam-Dussès, David (Chemical senses, 2012)
Within the multitude of chemical signals used by termites, the trail marking by means of pheromones is ubiquitous. Chemistry and biology of the trail-following communication have been described in more than 60 species from all families except for the Neotropical Serritermitidae. The chemical ecology of Serritermitidae is of special interest not only as a missing piece of knowledge on the diversity and evolution of isopteran pheromones but also because it may contribute to the debate on the phylogenetic position of this family, which is still unresolved. Therefore, we aimed in this study to identify the trail-following pheromone of the serritermitid Glossotermes oculatus. Based on a combined approach of analytical chemistry, electrophysiology, and behavioral bioassays, we propose (10Z,13Z)-nonadeca-10,13-dien-2-one to be the trail-following pheromone of G. oculatus, secreted by the sternal gland of pseudergates. Thus, we report on a new termite trail-following pheromone of an unexpected chemical structure, a ketone with 19 carbons, contrasting with unsaturated alcohols containing 12 carbons as trail-following pheromones in other advanced termite families. In addition to this unique trail-following pheromone, we also describe the sternal gland in pseudergates as an organ of unusual shape, size, and structure when compared with other isopteran species. These results underline the peculiarity of the family Serritermitidae and prompt our interest in the chemistry of pheromones in the other genus of the family, Serritermes.
Keywords: exokrinní žlázy; Behavior, Animal; Animals; Pheromones; chování zvířat; Fatty Acids, Unsaturated; feromony; Isoptera; Biological Assay; nenasycené mastné kyseliny; biotest; Exocrine Glands; zvířata